Direct and Indirect Carbon Footprint Assessment in The Construction Stage of Residential Buildings - Nava Rashed; Mazaher Moeinaddini; Ali Kazemi (Sustainable Earth Trends)
The construction industry, the leading cause of global greenhouse gas emissions, is responsible for at least 37 percent of global emissions. In Iran, greenhouse emissions in the construction sector between 1990 and 2020 have increased from 0.73 to 1.44 tons of carbon dioxide equivalent per person per year. The purpose of the current study is to investigate the direct and indirect carbon footprints for one square meter of the residential building built-area. The system boundary is “gate to gate,” and its functional unit is “one square meter of the residential building built-area.” Data selection was carried out using the checklist and literature review methods. The carbon footprint assessment was conducted using the IPCC 2013 model and the ReCiPe method. Concrete is the most substantial contributor to carbon footprint among all building materials. The results show that the total, direct, and indirect carbon footprint for one square meter of the residential building built-area is 445, 436, and 9 kgCO2e/m2, respectively. The building’s “excavation, foundation, and framing” phase mainly contribute to the indirect carbon footprint among building construction phases. The carbon footprint for each square meter of the residential building construction is related to different factors, such as total building area, type of buildings, material transportation distance, and type of building materials used.